Optimalisasi Germas Melalui Kader ‘Aisyiyah dalam Program Eliminasi Tuberculosis Paska Terapi TB - Majdawati, Ana; Inayati, Inayati (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Post TB patients are Tuberculosis (TB) patients who have received anti-TB drugs (OAT) and are declared cured. Evaluation is important, because the chance of relapse is 5-10x compared to non-TB, drug-resistant TB, and Post TB Obstruction Syndrome (SOPT). The data showed that 56.41% post TB was still symptomatic and 88.5% had findings of chest radiographic lesions and 78.2% had fibrosis. The incidence of TB in Mergangsan Yogyakarta District is quite high with dense settlements. This community service involves TB cadres' Aisyiyah who have collaborated with TB-related health centers. The results of the initial interview, the obstacles encountered in the field: 1). TB cadres' Aisyiyah are limited to finding new TB cases, evaluation of post TB patients is rarely done; 2) lack of understanding and the need for refreshing TB, post TB and its complications; 3). Communication limitations. The aim of this community service is to optimize the duties and roles of TB cadres' Aisyiyah in TB cases which includes evaluation of post TB patients. Activities carried out, socialization of community service based on Focus Group Discussion (FGD), training on filling out post TB investigation sheets. Face-to-face activities during the Covid 19 pandemic are limited to 11 representative cadres who can then pass on their knowledge to the public. Evidence of the success of community service is filling out the complete investigation sheet by cadres on 54 post-TB patients. This data can be used as an important follow-up for Mergangsan District stakeholders.